Green Tea Polyphenol Epigallocatechin-Gallate in Amyloid Aggregation and Neurodegenerative Diseases - Fernandes, Luiza; Cardim-Pires, Thyago R.; Foguel, Debora; Palhano, Fernando L. (Frontiers in Neuroscience, 2021)
The accumulation of protein aggregates in human tissues is a hallmark of more than 40 diseases called amyloidoses. In seven of these disorders, the aggregation is associated with neurodegenerative processes in the central nervous system such as Alzheimer's disease (AD), Parkinson's disease (PD), and Huntington's disease (HD). The aggregation occurs when certain soluble proteins lose their physiological function and become toxic amyloid species. The amyloid assembly consists of protein filament interactions, which can form fibrillar structures rich in β-sheets. Despite the frequent incidence of these diseases among the elderly, the available treatments are limited and at best palliative, and new therapeutic approaches are needed. Among the many natural compounds that have been evaluated for their ability to prevent or delay the amyloidogenic process is epigallocatechin-3-gallate (EGCG), an abundant and potent polyphenolic molecule present in green tea that has extensive biological activity. There is evidence for EGCG´s ability to inhibit the aggregation of α-synuclein, amyloid-β, and huntingtin proteins, respectively associated with PD, AD, and HD. It prevents fibrillogenesis (in vitro and in vivo), reduces amyloid cytotoxicity, and remodels fibrils to form non-toxic amorphous species that lack seed propagation. Although it is an antioxidant, EGCG in an oxidized state can promote fibrils' remodeling through formation of Schiff bases and crosslinking the fibrils. Moreover, microparticles to drug delivery were synthesized from oxidized EGCG and loaded with a second anti-amyloidogenic molecule, obtaining a synergistic therapeutic effect. Here, we describe several pre clinical and clinical studies involving EGCG and neurodegenerative diseases and their related mechanisms.